2019
DOI: 10.1111/jre.12678
|View full text |Cite
|
Sign up to set email alerts
|

Oral supplementation with p‐coumaric acid protects mice against diabetes‐associated spontaneous destruction of periodontal tissue

Abstract: Objective Dietary bioactive materials having anti‐inflammatory and antioxidant potentials are able to inhibit diabetes‐associated periodontal complications. Although numerous studies indicate that administration of p‐coumaric acid (p‐CA) ameliorates diabetes and diabetes‐related complications, the roles of p‐CA on periodontal tissue destruction in diabetic mice and the possible mechanisms therein are not completely understood. In this study, we evaluated whether supplementation with p‐CA protects mice against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Some of the major issues associated with PT were the tissue hypoxia, oxidative stress and relative vasospasm which in turn, determines increased coagulation and endothelial injury, damage of vascular endothelial cells, and finally periodontal tissue destruction [ 44 ]. Consequently, some evidence has been suggested that periodontal infection mediated by some pathogens such as A. actinomycetemcomitans may accelerate PT and endothelial damage and inflammatory response orchestrated through oxidative stress pathways [ 45 , 46 ], especially in obese patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the major issues associated with PT were the tissue hypoxia, oxidative stress and relative vasospasm which in turn, determines increased coagulation and endothelial injury, damage of vascular endothelial cells, and finally periodontal tissue destruction [ 44 ]. Consequently, some evidence has been suggested that periodontal infection mediated by some pathogens such as A. actinomycetemcomitans may accelerate PT and endothelial damage and inflammatory response orchestrated through oxidative stress pathways [ 45 , 46 ], especially in obese patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ferulic acid also increased glucokinase activity (Jung et al, 2007) and decreased glucose-6-phosphatase and phosphoenolpyruvate carboxykinase activities in liver (Son, Rico, Nam, & Kang, 2011 (Pei, Ou, Huang, & Ou, 2016). The supplementation of p-coumaric acid can prevent bone loss (Yamaguchi, Uchiyama, & Lai, 2007), inhibit diabetes-associated spontaneous destruction of periodontal tissue by (Bhattarai et al, 2019), and alleviate diabetic nephropathy in diabetic animals (Zabad, Samra, & Eissa, 2019).…”
Section: Hydroxycinnamic Acidsmentioning
confidence: 98%
“…p ‐Coumaric acid shows antidiabetic activity by reducing the intestinal absorption of carbohydrate, modulating glucose metabolism enzymes, improving β‐cell function, stimulating insulin secretion, increasing insulin sensitivity, activating AMP‐activated protein kinase, inhibiting adipogenesis and gluconeogenesis, and enhancing antioxidant potential and anti‐inflammation effects (Pei, Ou, Huang, & Ou, 2016). The supplementation of p ‐coumaric acid can prevent bone loss (Yamaguchi, Uchiyama, & Lai, 2007), inhibit diabetes‐associated spontaneous destruction of periodontal tissue by (Bhattarai et al., 2019), and alleviate diabetic nephropathy in diabetic animals (Zabad, Samra, & Eissa, 2019).…”
Section: Mechanisms Of Dietary Polyphenols As Antidiabetic Agentsmentioning
confidence: 99%
“…Chronic inflammatory responses also contribute to a mild and prolonged production of ROS leading to oxidative damages to cells and tissues [13]. Similarly, periodontitis, a chronic periodontal inflammatory disease, involves an excessive ROS generation in the periodontium [14,15]. Therefore, oxidative stress might be the key mediator in DM-associated periodontal destruction, as well as in hyperglycemia-related systemic disorders.…”
Section: Introductionmentioning
confidence: 99%